Pengenalan Identitas Budaya Nusantara Lewat Buku Mewarnai “The Time Machine Coloring Book Bernostalgia dengan Warna” - Kusumohendrarto, Raden Hadapiningrani; Fitri, Nofria Doni; Sani, Muhammad Nur (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2023)
In everyday life, a person will experience psychological ups and downs, both physically and spiritually. It can cause a person to experience fatigue, boredom, and stress. In response to this, there are many ways you can do it, one of which is by coloring an illustration book. The coloring illustration book entitled